Transitions to Early Care and Education
XVI, 204 p.
Keywords: Transitions to new educational experiences are a universal rite of passage encountered by children worldwide. This volume in the Educating the Young Child: Advances in Theory and Research, Implications for Practice series provides early childhood educators with a resource that focuses on the transitions that young children make to early care and education settings, along with the issues that surround this important time in their lives. New experiences, such as the start of formal schooling, mark important and exciting events that also evoke different reactions from children and their families. The diverse experiences, traits, and needs exhibited by young children provide early childhood educators with what may be a potentially challenging role. With an international focus, the purpose of Transitions to Early Care and Education: International Perspectives on Making Schools Ready for Young Children is to communicate an enlarged view of the transition process in order to appreciate and honor the promise and potential of all children worldwide. Contributing to this volume are a group of distinguished researchers, practitioners, and educators in the field of early childhood education. Their collective expertise is shared with those who are committed to educating and caring for young children and the families they serve.